2007
DOI: 10.1038/sj.jcbfm.9600511
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Mechanisms Involving Epoxyeicosatrienoic Acids, Adenosine Receptors, and Metabotropic Glutamate Receptors in Neurovascular Coupling in Rat Whisker Barrel Cortex

Abstract: Adenosine, astrocyte metabotropic glutamate receptors (mGluRs), and epoxyeicosatrienoic acids (EETs) have been implicated in neurovascular coupling. Although A 2A and A 2B receptors mediate cerebral vasodilation to adenosine, the role of each receptor in the cerebral blood flow (CBF) response to neural activation remains to be fully elucidated. In addition, adenosine can amplify astrocyte calcium, which may increase arachidonic acid metabolites such as EETs. The interaction of these pathways was investigated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 41 publications
5
83
3
1
Order By: Relevance
“…The selective P450 epoxygenases inhibitor MS-PPOH significantly diminished the perfusion response (Ϫ39.0 Ϯ 4.5%, p Ͻ 0.001) (Fig. 4 B), a reduction remarkably similar to that reported after superfusion of the same compound for 1 or 2 h over the sensory cortex (Ϫ38%; Shi et al, 2008). Considering that astrocytes also express glutamate and GABA-A receptors (Conti et al, 1997;Cahoy et al, 2008), which activation by selective agonists induces vasodilatation independently of spiking activity (Fergus and Lee, 1997;Zonta et al, 2003;Lovick et al, 2005), we examined the relationship between EETs and excitatory and inhibitory neurotransmission.…”
Section: Astroglial Messengers As Intermediaries For Both Inhibitory supporting
confidence: 60%
See 2 more Smart Citations
“…The selective P450 epoxygenases inhibitor MS-PPOH significantly diminished the perfusion response (Ϫ39.0 Ϯ 4.5%, p Ͻ 0.001) (Fig. 4 B), a reduction remarkably similar to that reported after superfusion of the same compound for 1 or 2 h over the sensory cortex (Ϫ38%; Shi et al, 2008). Considering that astrocytes also express glutamate and GABA-A receptors (Conti et al, 1997;Cahoy et al, 2008), which activation by selective agonists induces vasodilatation independently of spiking activity (Fergus and Lee, 1997;Zonta et al, 2003;Lovick et al, 2005), we examined the relationship between EETs and excitatory and inhibitory neurotransmission.…”
Section: Astroglial Messengers As Intermediaries For Both Inhibitory supporting
confidence: 60%
“…4C, 6C). These observations pointed to NMDA and GABA-A receptors contributing to the evoked CBF response, at least partly through distinct pathways, notwithstanding the glutamate effects mediated through receptors other than NMDA, such as mGluRs and AMPA/kainate receptors (Norup Nielsen and Lauritzen, 2001;Zonta et al, 2003;Lovick et al, 2005;Gsell et al, 2006;Shi et al, 2008; this study). We similarly combined COX-2 inhibition and GABA-A receptor blockade, but this failed to further impair the hyperemic response compared with COX-2 inhibition alone (Ϫ51.9 Ϯ 9.4% vs Ϫ51.2 Ϯ 8.0%) (Figs.…”
Section: Independent Contribution Of Excitatory and Inhibitory Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in CBF ( n  = 7–8 mic in each group) were assessed in three trials (5‐ to 10‐min intervals). CBF responses to whisker stimulation were repeated in the presence of the following inhibitors administered topically onto the brain surface of separate groups of animals: HET0016 (inhibitor of 20‐hydroxyeicosatrienoic acid (20‐HETE) production, 10 −6  mol L −1 for 30 min; Cayman Chemicals, Ann Arbor, MI, USA) (Liu et al ., 2008), MS‐PPOH (inhibitor of EET production, 20 × 10 −6  mol L −1 for 30 min; Cayman Chemicals) (Shi et al ., 2008), L‐NAME (N ω ‐Nitro‐L‐arginine methyl ester, inhibitor of nitric oxide synthase, 10 −4  mol L −1 for 20 min; Sigma‐Aldrich, St. Louis, MO, U.S.A.), apocynin (inhibitor of NADPH oxidases, 3 × 10 −4  mol L −1 for 30 min; Cayman Chemicals), fluoroacetate sodium (inhibitor of the tricarboxylic acid cycle predominantly in glial cells, 10 −4  mol L −1 min; Sigma‐Aldrich, St. Louis, MO, U.S.A.) (Fonnum et al ., 1997; Lecrux et al ., 2012), indomethacin (cyclooxygenase inhibitor, 5 × 10 −4  mol L −1 ; Sigma‐Aldrich, St. Louis, MO, U.S.A.) (Kitaura et al ., 2007), MPEP (6‐Methyl‐2‐(phenylethynyl)pyridine hydrochloride, group I metabotropic glutamate receptors (mGluR) subtype 5 antagonist, 5 × 10 −5  mol L −1 ) (Zonta et al ., 2003), and the NMDA (N‐methyl‐D‐aspartate) receptor antagonist D‐APV (D‐2‐Amino‐5‐Phosphonovaleric acid, 5 × 10 −5  mol L −1 ; Cayman Chemicals) (Stobart et al ., 2013). In a separate series of experiments ( n  = 8 in each group), CBF responses to topical administration of L‐glutamate (500 μmol L −1 ) (Hall et al ., 2014) were determined in the absence and presence of MPEP (5 × 10 −5  mol L −1 ) and D‐APV (5 × 10 −5  mol L −1 ) (Stobart et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Also in cultured cortical astrocytes, TRPV4 channels form complexes with aquaporin 4 to regulate cell volume responses to hypoosmotic stress (12). Notably, it has been shown that TRPV4 channels in other preparations are activated by epoxyeicosatrienoic acids (EETs) (13)(14)(15), which have been implicated in NVC (16)(17)(18) and reportedly stimulate Ca 2+ influx in rat cortical astrocytes (19,20). TRPV4 channels are thermosensitive, osmosensitive, and mechanosensitive, and thereby mediate processes by which cells sense and respond to environmental cues (21)(22)(23)(24) (25)(26)(27)(28)(29).…”
Section: Calcium | Parenchymal Arteriolementioning
confidence: 99%